Don Quijote y los molinos de viento en América Latina - Quijano, Aníbal (2006)
The author reviews the singularity of the impact of the colonialism and globalism in Latin America. He examines in particular the perspective of eurocentrism and the clash between democracy, knowledge and historical memory. The author conducts a systematic review of the historical production of Latin America and the destruction and redefinition of the past to go on to examine the characteristics of the new pattern of power, race and global social domination.